Metabolism of albendazole, ricobendazole and flubendazole in Haemonchus contortus adults: Sex differences, resistance-related differences and the identification of new metabolites - Stuchlíková, Lucie Raisová; Matoušková, Petra; Vokřál, Ivan; Lamka, Jiří; Szotáková, Barbora; Sečkařová, Anna; Dimunová, Diana; Nguyen, Linh Thuy; Várady, Marián; Skálová, Lenka (International journal for parasitology. Drugs and drug resistance, 2018)
Haemonchus contortus (family Trichostrongylidae, Nematoda), a hematophagous gastrointestinal parasite found in small ruminants, has a great ability to develop resistance to anthelmintic drugs. We studied the biotransformation of the three benzimidazole anthelmintics: albendazole (ABZ), ricobendazole (albendazole S-oxide; RCB) and flubendazole (FLU) in females and males of H. contortus in both a susceptible ISE strain and resistant IRE strain. The ex vivo cultivation of living nematodes in culture medium with or without the anthelmintics was used. Ultrasensitive UHPLC/MS/MS analysis revealed 9, 7 and 12 metabolites of ABZ, RCB and FLU, respectively, with most of these metabolites now described in the present study for the first time in H. contortus. The structure of certain metabolites shows the presence of biotransformation reactions not previously reported in nematodes. There were significant qualitative and semi-quantitative differences in the metabolites formed by male and female worms. In most cases, females metabolized drugs more extensively than males. Adults of the IRE strain were able to form many more metabolites of all the drugs than adults of the ISE strain. Some metabolites were even found only in adults of the IRE strain. These findings suggest that increased drug metabolism may play a role in resistance to benzimidazole drugs in H. contortus.
Keywords: biochemické jevy; Biochemical Phenomena; Drug Resistance; Male; Biotransformation; Benzimidazole; sexuální faktory; tandemová hmotnostní spektrometrie; Haemonchiasis; Mebendazole; mužské pohlaví; ovce; nemoci ovcí; Sheep; léková rezistence; Anthelmintics; Animals; biotransformace; Drug metabolism; ženské pohlaví; Sheep Diseases; Drug resistance; anthelmintika; zvířata; Sex Factors; albendazol; Nematode; Tandem Mass Spectrometry; hemonchóza; Albendazole; Female; Haemonchus; mebendazol